A legal analysis of the social security rights of domestic workers in South Africa : issues and challenges - Senyolo, Matome Johannes (My University, 2022)
This study discusses the legal analysis of social security rights of domestic workers in the South African social security law. The notion social security is concerned with the protection of individuals during the happening of certain event such as unemployment, maternity, disability, old age, sickness, and death. For the purpose of this study, social insurance schemes which arise from the employment relationship will be explored. It is submitted that domestic workers like any other employees should also be afforded social security protection as envisaged in the Constitution of the Republic of South Africa, 1996 (the Constitution). Therefore, domestic workers must also be provided social security rights arising out of their employment. Thus, the research process will involve thorough analysis of statutes, case law, textbooks and scholarly articles dealing with the social security law protection afforded to domestic workers, in particular the social insurance component of social security. For an exceptionally long time, domestic workers have been excluded from the formal employment sector, which followed that they were automatically excluded from social security protection. Despite section 9 of the Constitution, this espouses non-discrimination and equal treatment of all the workers in South Africa. To this end, there is no comprehensive social security system in South Africa that is capable of providing adequate social protection to domestic workers. For example, most domestic workers have no pension fund, and some are not registered with Unemployment Insurance fund and Compensation for Injuries and Diseases schemes.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2022
Keywords: Social security; Social Insurance; Domestic Work; Domestic Workers; Employee; Social security; Household employees; Insurance -- Social aspects; Household employees -- South Africa; Social security -- Law and legislation -- South Africa; Unemployment insurance -- South Africa